POST-TRAUMATIC GROWTH AS THE BASIS OF PSYCHOLOGICAL SUPPORT OF VETERANS OF THE RUSSIAN-UKRAINIAN WAR: REVIEW OF RESEARCH (Psychology Travelogs, 2023)
Prolonged war events in Ukraine have become powerful psycho-traumatic factors for all strata of the country's population. In particular, the war actualized the problem of post-traumatic stress disorder (PTSD) among persons who directly took part in a combat conflict. Every year, the ranks of veterans increase by several thousand. The most acute psychological problem of the war and post-war society is the return of military personnel, including veterans, to the conditions of peaceful life. All this is directly related to the resocialization of the individual, the actualization of the need for it, the identification of the individual's resources that contribute to the process of post-traumatic growth, as the transition of possibility into reality. In this regard, the question arises whether social negativity can change under the influence of overcoming traumatic events, and if so, how exactly.The article analyzes the phenomenon of post-traumatic growth (PTG). An attempt to conceptualize the definitions that reveal the essence of PTSD in the article aims to organize the terminology. An overview of existing models of post-traumatic growth as an effective tool for psychological support of veterans of the Russian-Ukrainian war is provided: the functional-descriptive model of R.G. Tedeschi and L.G. Calhoun; person-centered model of S. Josef; biopsychosocial model M. Christopher; psychological and philosophical model of R. Papadopulos. A number of views regarding the possibilities of implementing the theory of PTZ in psychological support with veterans, participants in hostilities, military, etc. are outlined.
Keywords: mental trauma; post-traumatic growth; positive changes; transformation; theoretical model; psychological consequences of trauma; psychotherapy